Faith and the founders of the American republic - Dreisbach, Daniel L.; Hall, Mark David (Oxford University Press, 2014)
Even before the founders were dead and buried, the American public had developed an extraordinary curiosity about their faith commitments (or lack thereof) and the influence of religion on the constitutional republic they established. This volume offers essays on a variety of religious views and beliefs that shaped late-eighteenth-century public life, such as the contribution of evangelical denominations to advancing religious liberty.